2021
DOI: 10.3390/ma14195903
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Properties of Composite Titanium Nitride Layers on the AZ91D Magnesium Alloy Using Hydrothermal Treatment

Abstract: Coating magnesium alloys with nitride surface layers is a prospective way of improving their intrinsically poor surface properties; in particular, their tribological and corrosion resistance. These layers are usually produced using PVD methods using magnetron sputtering or arc evaporation. Even though the thus-produced layers significantly increase the wear resistance of the alloys, their effects on corrosion resistance are unsatisfactory because of the poor tightness, characteristic of PVD-produced products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [9,10] In Figure 2b, it can be observed that there are white droplets and pits on the surface of the TiN coating. This is due to the intrinsic characteristics of the deposition technique.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [9,10] In Figure 2b, it can be observed that there are white droplets and pits on the surface of the TiN coating. This is due to the intrinsic characteristics of the deposition technique.…”
Section: Resultsmentioning
confidence: 97%
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [ 9,10 ]…”
Section: Resultsmentioning
confidence: 99%
“…Any violation of the continuity of the layer under the influence of mechanical factors, similar to the natural, leaking defects of the structure, will result in the formation of corrosion microcells and, as a result, accelerated destruction of the layer as a result of galvanic corrosion. Therefore, in order to ensure the service life of products made of magnesium alloys exposed to corrosion, apart from corrosion resistance, high mechanical resistance is also required [23]. Therefore, a number of mechanical tests were performed.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the main objective of the study was to verify the susceptibility of zirconium nitride-based layers to hydrothermal sealing. The origin of the concept of final sealing of zirconium nitride composite layers was in earlier works on the hybrid production of tight, highly resistant to corrosion and wear, TiN-Ti-Al titanium nitride composite layers, which showed outstanding effectiveness [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Heated to a certain pressure and temperature in the reactor, water molecules will gain some activity, which can react with some active metals. Through the chemical reactions, a hydroxide film layer can be directly formed on the alloy surface [19]. The film layer can prevent corrosion, avoiding the corrosion of the metal substrate by external media to a certain extent.…”
Section: Introductionmentioning
confidence: 99%